The evaluation of coated granules to mask the bitter taste of dihydroartemisinin - Yasser Shahzad; Syed Nisar Hussain Shah; Shabbar Atique; Muhammad Tayyab Ansari; Farooq Bashir; Talib Hussain (Universidade de São Paulo, 2011)
The purpose of this study was to mask the bitter taste imparted by dihydroartemisinin (DHA) by the use of different coating materials. Trial-1 and trial-2 were conducted to prepare the DHA granules. The granules produced from trial-1 were irregular in shape and smaller in size while the trial-2 granules were more regular and larger in size. The granules obtained from both trials were then coated with two different coating methods, namely A and B, depending upon coating material. The trial-2 granules showed better flow properties than trial-1 granules. In vitro dissolution studies in phosphate buffer at pH 6.8 revealed that granules of trial-2B released only 34% ± 3 DHA in two minutes compared with trial-1A (57% ± 2), trial-1B (48% ± 2) and trial-2A (53% ± 7). The pleasant taste perception (PTP) test also confirmed the taste masking efficacy of trial-2B (P < 0.05). Scanning electron microscopy (SEM) revealed the more regular and smooth surface of trial-2B granules. In addition, the differential thermal and thermogravimetric analysis (TG-DTA) confirmed no interaction between the materials and pure DHA. DHA has shown its characteristic peaks in the x-ray diffraction (XRD) patterns which were also prominent in all the granules. In conclusion, the granules obtained from trial-2B displayed considerable decrease in the bitter taste of DHA thereby fulfilling the purpose of this study. O objetivo deste estudo foi o de mascarar o gosto amargo característico da diidroartemisinina (DHA) pelo uso de diferentes materiais de revestimento. Experimento-1 e experimento-2 foram realizados para preparar grânulos de DHA. Os grânulos produzidos pelo experimento-1 mostraram-se irregulares e menores se comparados aos obtidos pelo experimento-2, que foram mais regulares e maiores. Os grânulos obtidos em ambos os experimentos foram, então, revestidos por dois métodos distintos de revestimento, designados como A e B, dependendo do material de revestimento empregado. Os grânulos do experimento-2 mostraram melhor propriedade de fluxo que os obtidos no experimento-1. Estudos de dissolução in vitro em tampão fosfato pH 6,8 revelaram que grânulos do experimento-2B liberaram apenas 34% ± 3 da DHA em dois minutos se comparado com experimento-1A (57% ± 2), experimento-1B (48% ± 2) e experimento-2A (53% ± 7). A Análise Sensorial quanto ao sabor (Pleasant Taste Perception - PTP) também confirmou a eficácia do experimento-2B (P <0,05) em mascarar o gosto amargo da DHA. Microscopia Eletrônica de Varredura (SEM) revelou a superfície mais regular e lisa dos grânulos obtidos pelo experimento-2B. Além disso, Análise Termogravimétrica e Análise Térmica Diferencial (TG-DTA) confirmaram que não há nenhuma interação entre os materiais e a DHA pura. DHA mostrou seus picos característicos na Difração de Raios X (XRD) em padrões que também foram proeminentes em todas as amostras. Em conclusão, os grânulos obtidos pelo experimento-2B exibiram diminuição considerável no gosto amargo da DHA, o que era o propósito deste estudo.